1996
DOI: 10.1093/infdis/173.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Mucosal Antibodies by Live Attenuated and Inactivated Influenza Virus Vaccines in the Chronically III Elderly

Abstract: Induction of local antibody responses to influenza A virus hemagglutinin by coadministration of two vaccines was investigated. Fifty elderly nursing home residents received inactivated trivalent influenza virus vaccine intramuscularly and simultaneously were randomized to receive either bivalent live attenuated influenza A virus vaccine or saline placebo intranasally in a blinded fashion. More significant increases in anti-H1 and -H3 IgA antibodies were detectable in nasal wash specimens of subjects who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Parenterally administered (unadjuvanted) vaccines such as TIV do not effectively induce influenza-specific CD8 ϩ T cells or mucosal immune responses, two immune effectors capable of protecting the host (31,32). CD8…”
Section: Discussionmentioning
confidence: 99%
“…Parenterally administered (unadjuvanted) vaccines such as TIV do not effectively induce influenza-specific CD8 ϩ T cells or mucosal immune responses, two immune effectors capable of protecting the host (31,32). CD8…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of a certain level of serum HAI antibody response is predictive of protection, the absence of such responses following LAIV administration does not correlate with lack of protection, as high levels of efficacy and effectiveness occur with low serum HAI responses elicited by LAIV (41). The explanation for this imperfect correlation between serum antibody and protection may be because LAIV induces protection through other mechanisms, such as by stimulating mucosal immune responses in the respiratory tree (20)(21)(22). While efficacy of any type of influenza vaccine in HIV-infected children remains unproven, we observed that the relative antibody responses to LAIV and TIV in HIV-infected children were similar to those reported in children without HIV infection (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal administration of LAIV simplifies immunization and avoids the pain of intramuscular injection, thereby making LAIV more acceptable to most patients and avoiding missed opportunities because of deferred administration. Moreover, because of intranasal administration, LAIV has the potential to stimulate greater local anti-influenza immune responses than TIV (20)(21)(22). LAIV demonstrated greater reductions in influenza than TIV in HIV-uninfected children, against strains that were well-matched with strains in the vaccine, as well as against antigenically drifted strains not included in the vaccine administered (23)(24)(25)(26)(27)(28), and several studies have shown that the LAIV protective effect can extend beyond the year of administration (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…The inactivated virus vaccine is a better inducer of virus-specific serum antibody than the live ca vaccine. In contrast, live ca vaccines, apart from the advantage of painless nasal administration, also stimulate the induction of mucosal antibodies and cross-reactive cell-mediated immune responses, thus providing a broader and longer-lasting immunity (2,3,7,12,24). In children and healthy adults, serum hemagglutination inhibition antibodies and immunoglobulin G (IgG) and IgA antibodies to HA in respiratory secretions correlate with protection from infection (3,11,27).…”
mentioning
confidence: 99%